Kinesiology in swimming via multimedia - Soons, B.; de Belder, C.; Colman, V.; Persyn, U. (International Journal of Computer Science in Sport, 2002)
To help an expert to optimize a swimmer`s technique and dry land training, while preventing injuries, a so-called expert system, based on kinesiological research, is in development. The outputs of the research strategy, working hypotheses and results about propulsion concepts, balance and body characteristics (structure, flexibility and strength) have been implemented via multimedia, including animations.